PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. SEAFOOD NUSANTARA KABUPATEN TOLITOLI - Burhanuddin Burhanuddin; Samsidar Samsidar (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
The problem in this study is how much influence the motivation has on employee performance at PT. Seafood Nusantara Tolitoli Regency? The purpose of this study was to determine how much influence motivation on employee performance at PT. Seafood Nusantara Tolitoli Regency. This research was conducted at PT. Seafood Nusantara Tolitoli Regency. Data collection techniques by means of observation, interviews, and questionnaires. The population and sample in this study were employees of PT. Seafood Nusantara Tolitoli Regency, amounting to 35 people. The sampling technique in this study uses